Managing Emotions Can Shape Students' Polite Behavior Through Group Counseling Services - Diva Aprillia Haryono; Cristine Masada Hirashita Tobing; Sabrina Dachmiati (Asosiasi Asesmen Pendidikan (AAP), 2026)
Polite behavior among students is an essential aspect of character development that can be influenced by their ability to manage emotions effectively. The purpose of this study was to determine the significant effect of emotion management on students' polite behavior after participating in group counseling services. This study used a quantitative approach with experimental and survey methods. The research sample consisted of 58 students from class X PM 1 and X MP at SMK Al Makmur Jagakarsa, South Jakarta, who were selected through a One–Group Pretest-Posttest. The instruments used in the study included a questionnaire that had been modified from relevant studies and tested for validity and reliability, along with interview guides, observation sheets, and documentation to support data collection through triangulation. The data were analyzed using normality testing and the Paired Sample T-Test hypothesis test using SPSS Statistics Version 20. The results of the analysis showed a significance value (2-tailed) of 0.000 in the pre-test and post-test, which is less than 0.05. The results of this study indicate that group counseling services focused on improving students' understanding of managing emotions can shape polite behavior. The results of this study are useful in helping students understand and develop their emotional potential and shape themselves positively.